Analisis Faktor Risiko Keluhan Fatigue pada Pramudi BRT (Bus Rapid Transit) Transjakarta Tahun 2022 - Megaranti, Stefany Avelliana; Satrya, Chandra (National Journal of Occupational Health and Safety, 2022)
There were 508 cases of Transjakarta Bus accidents in 2021. Investigation results by the National Transportation Safety Committee (KNKT) revealed that one of the causes was driver fatigue. This study aims to describe fatigue complaints and analyze fatigue-related risk factors in Drivers of Transjakarta BRT (Bus Rapid Transit) and Non-BRT in 2022. This research is a quantitative study with an analytical descriptive research design. The research sample was 124 Drivers of Transjakarta BRT and Non-BRT. The independent variables in this study are work-related risk factors (Work Duration, Shift Work, Rest Time, Commuting Time, and Workload). The covariates in this study were worker-related risk factors (Age, Gender, BMI, Caffeine Consumption, Hypertension, Diabetes, and Sleep Quantity). This cross-sectional study used the Swedish Occupational Fatigue Index (SOFI) questionnaire to measure fatigue and the NASA-TLX questionnaire to measure workload. The data analysis is bivariate with the Chi-square test and multivariate with logistic regression. The study result showed that 48.4% (60) drivers experienced fatigue, and 55.6% (64) drivers did not experience fatigue. BMI, age, and sleep quantity have a significant relationship with fatigue. The most dominant work-related factor that affects fatigue is workload, although no significant relationship was found.